Árboles para Neiva (REVISTA NODO, 2008)
This article is part of an ongoing research called Strengthening of the Ecological Principal Structure as of the identification and selection of species for urban tree planting, taking place in seven (7) Colombian cities: Cúcuta, Bucaramanga, Villavicencio, Palmira,Ibagué, Neiva and Popayán. Herein are the results for the city of Neiva.
Keywords: Urban tree planting; Ecological Principal Structure; biological corridors